Nauczanie języka obcego w grupie uczniów niewidomych i słabowidzących – przegląd badań - Jedynak, Małgorzata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The paper concerns foreign language typhlomethodology and presents an overview of available research findings in the field, arranged in chronological order. The studies discussed in the paper have insight into either first language acquisition or foreign language learning by visually impaired learners. The former shed light on the potential problems the visually impaired might have while learning foreign languages. The problems might emerge both in the phonological or semantic domain. The latter, in turn, discuss such issues as the use of foreign language vocabulary learning strategies and the role of affective factors which facilitate the language learning process. Nowadays the European Union promotes ‘Languages to All’ principle, i.e. teaching languages to all groups of learners, regardless of their disabilities and impairments, preferably in inclusive education setting. Therefore, foreign language teachers should be acquainted with the research findings and their implications presented herein.